Analisis Rasio Keuangan Untuk Menilai Kinerja Keuangan Pada PT. Aneka Tambang Tbk yang Terdaftar di BEI Periode 2017-2021 - Ficka Adelya; M. Imam Sundarta (Komunitas Dosen Indonesia, 2024)
This study aims to determine and assess financial performance using liquidity ratios, solvency ratios, and profitability ratios at PT. Aneka Tambang Tbk. The data collection method in this study is to use secondary data, namely financial reports from 2017-2021. This study analyzed data using descriptive methods with a qualitative approach. Based on the results of the research, it shows that the average value of the liquidity ratio in 2017-2021 is in an illiquid state because it is below the industry standard, which means that the company has not been able to manage its assets optimally, so that the company's short-term debt is greater than the company's current assets. The solvency ratio shows that the average value in 2017-2021 is in a solvable state because it is below the industry standard, which means the company is capable of meeting its debts. And the profitability ratio shows that in 2017-2021 it is not profitable because it is below industry standards, which means that the company's ability to generate good profits from sales, total assets and total equity of the company is still not good because the cost of goods sold continues to increase.